The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.ophtha.2019.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus Natural Progression

Abstract: Purpose: We set out to describe the natural history of keratoconus. We included untreated patients, and our key outcome measures were vision, refraction, and corneal curvature. Clinical Relevance: Keratoconus affects 86 in 100 000 people, causing visual loss due to increasing irregular corneal astigmatism, and the quality of life declines in patients. Interventions are used to stabilize the disease or improve vision, including corneal cross-linking (CXL) and grafting, but these carry risks. Detailed knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(106 citation statements)
references
References 67 publications
5
79
4
1
Order By: Relevance
“…The geometric decompensation that causes the conical shape is localized mainly in the temporal lower quadrant of the mean peripheral region [2] due to a loss of tenacity that the corneal structure suffer by a reorientation of its anatomophysiology [3]. In addition, this morphologic decompensation inducts an increase of the high-order optical aberrations [4], showing the patients high values of irregular astigmatism and presenting as their main refractive sign the impossibility of a complete optical compensation of their ametropia by spherocylindrical lenses. Consequently, their corrected visual acuity will be diminished with respect to patients without corneal pathology [5].…”
Section: Introductionmentioning
confidence: 99%
“…The geometric decompensation that causes the conical shape is localized mainly in the temporal lower quadrant of the mean peripheral region [2] due to a loss of tenacity that the corneal structure suffer by a reorientation of its anatomophysiology [3]. In addition, this morphologic decompensation inducts an increase of the high-order optical aberrations [4], showing the patients high values of irregular astigmatism and presenting as their main refractive sign the impossibility of a complete optical compensation of their ametropia by spherocylindrical lenses. Consequently, their corrected visual acuity will be diminished with respect to patients without corneal pathology [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ferdi et al [15] conducted a systemic review and meta-analysis on keratoconus progression and concluded that patients aged less than 17 years, and those with a Kmax > 55 D, are at significantly greater risk of keratoconus progression. When we classified eyes according to an Rmin cut-off value of 6.13 mm (equivalent to 55.0 D) and age cut-off of 17 years, according to Ferdi's study, the incidence of CXL was 85.7% in the eyes of the younger age group with the lower Rmin values.…”
Section: Plos Onementioning
confidence: 99%
“…4,11 Cited risk factors include individual gene composition, ultraviolet and sun exposure, eye rubbing, gender, hormonal variation, age, atopy, floppy eyelid syndrome and parental education. 4,6,12 In addition, connective tissue disorders such as Ehler-Danlos syndrome, Marfan syndrome, Lonstein disease, Down syndrome and mitral valve prolapse are the most common associated disease conditions. 6 There is a huge disparity in access to eye care services, diagnostic equipment and management options between low-and high-income countries.…”
Section: Introductionmentioning
confidence: 99%